ANALYSIS OF PROFIT SHARING SYSTEM BEEF CATTLE BREEDING BUSINESS IN KLAMBIR V KEBUN HAMPARAN PERAK SUBDISTRICT DELI SERDANG DISTRICT - Wilda Rifki; Yusuf Leonard Henuk; Armyn Hakim Daulay; Yunilas .; Nevy Diana Hanafi (Jurnal Peternakan Integratif, 2017)
Abstrak. The purpose of this research was to know the management of profit sharing system in the area, to analyze the income and profit of the investor and the farmer and the percentage of the contribution of the livestock business in fulfilling the income of the farmer family. This research was conducted in Klambir V Kebun Hamparan Perak Subdistrict Deli Serdang District for 2 month from July 2017 until August 2017. This research used primary data and secondary data. The location of the research and the determination of the respondents was determined purposively. Respondents consisted of 35 people who were divided into three scales: 16 respondents  for 3-11 (small scale), 10 respondents for 12-20 (medium scale) and 9 respondents for scale > 20 (large scale) . The results showed that the profit sharing system that is implemented in Klambir V Kebun is a profit sharing system for bulls with 50:50 share of the results. The income received by the investor  and  the farmer is ​​different because in this business breeder farmers who spend for the maintenance of livestock while the investors only provide the livestocks germs. The bigger scale of business that the greater the income. The cattle breeding business with this profit sharing system has a value of r /c ratio > 1,  which means the business is feasible to cultivate. The contribution of livestock at each successive scale is 53.40%, 60.22% and 67.79%. Livestock can be categorized as a branch of business because it contributes 30-70% in fulfilling the household income.Keywords: profit sharing, beef cattle, income, profit